(untitled) (Clinics, 2022)
Objective: To evaluate the frequencies of iNKT cells and their subsets in patients with deep endometriosis. Methods: A case-control study was conducted between 2013 and 2015, with 73 patients distributed into two groups: 47 women with a histological diagnosis of endometriosis and 26 controls. Peripheral blood, endometriosis lesions, and healthy peritoneal samples were collected on the day of surgery to determine the frequencies of iNKT cells and subtypes via flow cytometry analysis. Results: The authors observed a lower number of iNKT (p = 0.01) and Double-Negative (DN) iNKT cells (p = 0.02) in the blood of patients with endometriosis than in the control group. The number of DN iNKT IL-17+ cells in the secretory phase was lower in the endometriosis group (p = 0.049). There was an increase in the secretion of IL-17 by CD4+ iNKT cells in the blood of patients with endometriosis and severe dysmenorrhea (p = 0.038), and severe acyclic pelvic pain (p = 0.048). Patients with severe dysmenorrhea also had a decreased number of CD4+ CCR7+ cells (p = 0.022). Conclusion: The decreased number of total iNKT and DN iNKT cells in patients with endometriosis suggests that iNKT cells play a role in the pathogenesis of endometriosis and can be used to develop new diagnostic and therapeutic agents.